Comparing the Effectiveness of the Qishah and Lecture Methods in Islamic Cultural History Instruction at Secondary Level - Amarsyah Siregar (Sufiya Journal of Islamic Studies, 2025)
This study aims to compare the effectiveness of the Qishah (storytelling) and lecture methods in teaching Islamic Cultural History at the secondary school level. Employing a mixed-methods approach with a convergent parallel design, quantitative data were gathered through student questionnaires and qualitative data through in-depth interviews with subject teachers. Quantitative data were analyzed descriptively and comparatively to examine differences in means, variances, and standard deviations between the two methods, while qualitative data were analyzed thematically to explore teachers’ insights and experiences in instructional practice. The findings indicate that both methods are effective in enhancing students’ understanding and engagement; however, the Qishah method demonstrates greater impact on affective and motivational dimensions by creating a more meaningful learning experience. Meanwhile, the lecture method remains valuable for reinforcing conceptual and structural comprehension.